The Pragmatic Transfer of Javanese Sojourners’ English in Conversation Strategies - Dwijani Ratnadewi (Ahmad Dahlan Journal of English Studies, 2020)
The use of home cultural schemas in English interactions in an English-speaking host country as a form of discrepancy leading to misunderstanding. This study investigated the pragmatic transfer phenomenon, namely the use of Javanese culture in English conversation. It aimed at finding an occurrence of pragmatic transfer in the Javanese English conversation in the host country; the conversation strategies the transfer takes place, and the tendency of pragmatic transfer in the conversational strategies. The data were collected through semi-structured interviews and field notes. The analysis used the narrative analysis using vital emergent themes based on the pragmatic transfer principle, the conversational strategy, and the Javanese norms. The result indicated the availability of negative and positive pragmatic transfer in four strategies: making the most of others’ praise, indirect response, denial over compliments, mitigating taboo or imposition marked with Javanese terms, idioms, and jargon insertion. Besides, motivation is an essential aspect that determines the existence of pragmatic transfer in English interactions.